2013
DOI: 10.1371/journal.pcbi.1003132
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Binding Profiles Reveal Cyclic Expression of Human Protein-coding Genes and Non-coding RNAs

Abstract: Cell cycle is a complex and highly supervised process that must proceed with regulatory precision to achieve successful cellular division. Despite the wide application, microarray time course experiments have several limitations in identifying cell cycle genes. We thus propose a computational model to predict human cell cycle genes based on transcription factor (TF) binding and regulatory motif information in their promoters. We utilize ENCODE ChIP-seq data and motif information as predictors to discriminate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…As one of the most important cellular processes, the cell cycle is precisely regulated in all organisms. Dysregulation of the cell cycle can lead to catastrophic cellular events, e.g., premature apoptosis or abnormal proliferation, which are causes of cancers 39 . We found that the lncRNA and miRNA regulated key components of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most important cellular processes, the cell cycle is precisely regulated in all organisms. Dysregulation of the cell cycle can lead to catastrophic cellular events, e.g., premature apoptosis or abnormal proliferation, which are causes of cancers 39 . We found that the lncRNA and miRNA regulated key components of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this gene set’s ability to infer E2F4’s regulatory activity level, we have used the gene set in conjunction with REACTIN to generate E2F4 iRASs in a cell cycle phase dataset [ 29 ], finding that E2F4 iRASs exhibits a periodic pattern and greatly outperforms E2F4 gene expression level in correlating with cell cycle phase (Figure 1 B). As E2F4 is a known critical regulator of the cell cycle [ 25 ], this result suggests that E2F4 iRASs reflect E2F4 functional activity and with much better accuracy than E2F4 gene expression level alone.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on the E2F4 signature, because we have previously identified it as being prognostic in breast cancer in a large-scale computational screening analysis [ 24 ]. Further, in other work we have found E2F4’s activity level to be the most important of all TFs in predicting cell cycle phase in the HeLa and K562 cell lines, suggesting an essential role for E2F4 in cell cycle regulation [ 25 ]. Beyond our work, it is broadly considered that E2F4 plays an important role in both cell cycle arrest [ 26 ] and in modulating cell proliferation [ 27 ].…”
Section: Introductionmentioning
confidence: 97%
“…Mis-regulation of the cell cycle can lead to catastrophic cellular events, e.g. premature apoptosis or abnormal proliferation of cells, which are the causes of cancers (Cheng et al 2013). We found that both the lncRNA and miRNA regulated the key components of this pathway.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 82%